Apoio social para pessoas convivendo com AIDS - Caixeta, Camila Roberto da Costa Borges (2010)
Acquired immunodeficiency syndrome (aids) is a chronic disease that may affect physical, emotional, intellectual, social and spiritual functions. The social support systems can minimize damage and improve the well-being of people living with this disease. The aim of this study was to identify and categorize the social support systems reported by people living with aids. A qualitative research approach was chosen, using concepts of social support as a theoretical reference. Ethical principles were followed with regards to research with human beings, according to international standards and the National Council of Ethics. Participants were eight people living with aids, who were randomly selected within categories of people most vulnerable to infection. Data was collected through deep interviews and field notes. Data analysis was done according to the social support framework; initial coding was done followed by focused coding of the interviews. The results showed the characteristics of the participants and the categories of social support systems mentioned in the statements: emotional, informational, instrumental and reinforcement. The main sources of support were: the family, especially mothers, and health professionals as sources of emotional support. Wife and partner, as well as friends and support institutions, were sources of emotional and instrumental support. The internet, selfhelp and membership groups offered informational support. Social security benefits and government policies were identified as instrumental support. Spirituality and religion appeared as a form of support for most of those living with aids. Self-help was characterized as reinforcement support. It is important to identify social support as a strategy for health promotion to reorient health services. The sources of social support can act in the integration of individuals into society, minimizing the risks of social exclusion and, therefore, of damage to their health.